Gambaran Premenstrual Syndrome pada Remaja Periode Akhir di Fakultas Kedokteran Universitas Sam Ratulangi - Lumingkewas, Charisma; Suparman, Eddy; Mongan, Suzanna P. (e-CliniC, 2021)
Abstract: Premenstrual syndrome (PMS) is the most common untreated disorder and a public health problem among women of reproductive age, which adversely affects mental well-being, quality of life, and academic achievement. This study was aimed to determine the premenstrual syndrome signs and symptoms most experienced by late adolescents. This was a descriptive and survey study using questionnaire distributed through google form to 142 female students from first and third semester of Faculty of Medicine Sam Ratulangi University academic year 2020/2021. The results showed that the most common type of PMS symptoms was psychological symptoms found in 136 respondents (95.8%); the most common behavioral symptom was fatigue in 93 respondents (65.5%), the most common physical symptom was acne in 122 respondents (85.9%); and the most psychological symptom was mood swing in 125 respondents (88%). In conclusion, the most common premenstrual syndrome symptom found in late adolescent at the Faculty of Medicine Sam Ratulangi University according to the type of symptom was psychological symptom.Keywords: premenstrual syndrome, adolescentÂ Abstrak: Premenstrual syndrome (PMS) merupakan kelainan umum yang tidak diobati dan masalah kesehatan masyarakat di kalangan wanita usia reproduksi, yang berdampak buruk pada kesejahteraan mental, kualitas hidup dan prestasi akademik. Penelitian ini bertujuan untuk mengetahui tanda dan gejala PMS yang paling banyak dialami remaja periode akhir. Penelitian ini menggunakan metode survei deskriptif dengan alat kuesioner yang dibagikan melalui google form pada 142 mahasiswi semester 1 dan 3 Fakultas Kedokteran Universitas Sam Ratulangi tahun ajaran 2020/2021. Hasil penelitian mendapatkan jenis gejala PMS yang paling banyak dialami ialah gejala psikologis pada 136 responden (95,8%), gejala perilaku yang paling banyak dialami ialah kelelahan pada 93 responden (65,5%), gejala fisik yang paling banyak dialami ialah muncul jerawat pada 122 responden (85,9), dan gejala psikologis yang paling banyak dialami ialah mood swing pada 125 responden (88%). Simpulan penelitian ini ialah gambaran PMS pada remaja periode akhir di Fakultas Kedokteran Universitas Sam Ratulangi yang paling banyak dialami menurut jenis gejala ialah gejala psikologis.Kata kunci: premenstrual syndrome, remajaÂ